The Information Policy in the Activities of a Modern Enterprise - A. Vorobyova, Olga; E. Egorova, Axiniya; Thanh Nguyen, Phong; Hoang Thuy To Nguyen, Quyen Le; Bich Huynh, Vy Dang (International Journal of Psychosocial Rehabilitation, 2024)
In modern conditions, a dynamically changing external environment, scientific and technological progress, and a constant reduction in the life cycle of a product are forcing enterprises to look for sources to increase the efficiency of their activities. Work with information; the ability to use it productively is the main condition for the success of any enterprise. The main property of information, through which humanity has risen to the modern level of civilization, is its ability to endlessly replicate without losing its original properties. No other nature resource has this property. Spending tremendous efforts to obtain new knowledge about the forces and laws of nature and directing this knowledge to the sphere of production, by replicating the results obtained, people repeatedly cover the costs of obtaining knowledge and receive additional benefits due to the additional involvement of nature forces in the production. The article is devoted to information policy, its evolution, and the impact on the efficiency of the enterprise. The article also considers the relationship of information policy with process management—a concept that changes the approach to enterprise management when an enterprise’s activity is considered as a continuous chain of business processes—and management—business process management.